Procrastination conceptualization as a personal phenomenon in the context of the brain and somatic mechanisms functioning - Chechel, Vladyslav; Zhuravlova, Olena (Psychological Prospects Journal, 2025)
Purpose. The article is devoted to the analysis of procrastination as a complex psychological and neurophysiological phenomenon. In particular, the article describes the biological factors associated with the development of a dilatory behavioural response. The relevance of the topic is due to the increasing prevalence of procrastination in the modern reality, characterised by multitasking, high pace of life and growing demands on personal productivity.Methods. The study used methods of theoretical analysis and a literature review on the topic, including neuroimaging, psychophysiology, cognitive and neuroscience data on motivation and emotions. Decision-making models and data on functional brain networks were also analysed.Results. The key role of the prefrontal cortex and limbic structures in decision-making, emotion regulation and self-control was revealed. It was found that a decrease in activity in areas such as the DLPFC or an increase in the activity of reward and avoidance systems (including the amygdala, insula) increase procrastination. It has been found that the strategy of obtaining immediate gratification and avoiding stressful tasks contributes to the formation of a cycle of procrastination. Procrastination also has a psychosomatic dimension - it is associated with increased stress levels, sleep problems, weakened immunity and a tendency to engage in health risk behaviours. It has also been noted that there is an inverse relationship between decreased self-efficacy and poor mental and physical health.Conclusions. Procrastination should be viewed as a multidimensional phenomenon determined by the interaction of cognitive, emotional and neurophysiological mechanisms. In light of current research, it is important to consider its impact not only on psychological functioning but also on physical health. Looking at procrastination from a neuroscientific perspective opens up new opportunities for developing effective therapeutic and preventive strategies, such as training emotion regulation, stimulating executive functions, or enhancing the ability to imagine the future in order to increase the value of tasks.